Penerapan Model Inkuiri untuk Meningkatkan Aktivitas dan Pemahaman Konsep Siswa - Titin, Titin; Yeni, Laili Fitri; Fauziah, Siti (Jurnal Pendidikan Matematika dan IPA, 2012)
This purpose of this research is to find out the implementation of inquiry model to improve the students` activity and comprehension of concept on the material about food digestion system to the eight year students (class VIII) of SMP Negeri 1 Sukadana in academic year 2008/2009. The sample of this research consists of one class that is class VIII A. The tool of data collecting forms essay test that consists 6 items. The essay test has been validated by 2 validators and it had reliability 0,47 or categorized sufficient. Based on the result of data analysis, the students` comprehension of concept on the material is 64,53% and includes good category. Meanwhile, the students` activity percentage is 85,15% and includes active category. Therefore, it can be concluded that the implementation of inquiry model can improve the students` activity and comprehension of concept on the material about food digestion system.